2015
DOI: 10.3126/jcmc.v4i3.11938
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on self care among COPD patients attending at Chitwan Medical College Teaching Hospital, Bharatpur

Abstract: Chronic obstructive pulmonary disease is a major cause of morbidity and mortality worldwide and global health concern. COPD self care knowledge is a cornerstone for self-management of chronic illness. The objective of this study was to find out the level of knowledge on self care among COPD patients. A descriptive, cross sectional design and purposive sampling was applied in which 182 patients were interviewed by using semi-structure interviews schedule at Chitwan Medical College, Teaching Hospital, Bharatpur.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
2
5
1
Order By: Relevance
“…In this community-based study, we identified that being uneducated, with a low level of family income (β = − 5.22, p = .002), and having one co-morbidity were all significantly associated with SMPs among the multi-morbid COPD patients of Nepal. Our finding is consistent with observations from a previous Nepalese study that concluded lack of education among the COPD patients contributed to poor SMPs such as incorrect use of inhalers [5], knowledge on self-care [6] and knowledge on COPD [7]. Patients with no education have poor functional health literacy and thus are more likely to have a poorer understanding of self-management skills including information management, symptoms management, daily lifestyle management, emotional management, and selfefficacy, in turn resulting in poor SMPs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this community-based study, we identified that being uneducated, with a low level of family income (β = − 5.22, p = .002), and having one co-morbidity were all significantly associated with SMPs among the multi-morbid COPD patients of Nepal. Our finding is consistent with observations from a previous Nepalese study that concluded lack of education among the COPD patients contributed to poor SMPs such as incorrect use of inhalers [5], knowledge on self-care [6] and knowledge on COPD [7]. Patients with no education have poor functional health literacy and thus are more likely to have a poorer understanding of self-management skills including information management, symptoms management, daily lifestyle management, emotional management, and selfefficacy, in turn resulting in poor SMPs.…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that this difference could be due to the difference in the instruments used to measure self-management practices. In this light, a hospital-based study from Nepal reported that 90.7% of COPD patients had a poor level of knowledge on the self-care of COPD [6]. In Nepal, the majority of the COPD patients seek services from the government or private hospitals because of the inadequacy of available services at the primary health care level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this community-based study, we identified that being uneducated, with a low level of family income (β=-5.22, p=.002), and having one co-morbidity were all significantly associated with SMPs among the multi-morbid COPD patients of Nepal. Our finding is consistent with observations from a previous Nepalese study that concluded lack of education among the COPD patients contributed to poor SMPs such as incorrect use of inhalers (5), knowledge on self-care (6) Our research found a negative association between low-level SMPs and the presence of more than one co-morbidity. In contrast, a study conducted by Bringsvor et al focusing on COPD patients that showed that the presence of co-morbidities was associated with poor self-management practices (32).…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that this difference could be due to the difference in the instruments used to measure self-management practices. In this light, a hospitalbased study from Nepal reported that 90.7% of COPD patients had a poor level of knowledge on the self-care of COPD (6). In Nepal, the majority of the COPD patients seek services from the government or private hospitals because of the inadequacy of available services at the primary health care level.…”
Section: Discussionmentioning
confidence: 99%